2004
DOI: 10.1002/zoo.20005
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the formation and maintenance of all‐male gorilla groups in captivity

Abstract: The social housing of males is of particular importance for captive managers of polygynous species. In this work, we highlight nine areas we believe are important to the successful formation and maintenance of all‐male gorilla groups. Although more data are still needed to complete our understanding of these groups, the general picture that emerges is that all‐male groups can be a functional social unit for male gorillas, the longevity of which might be improved by careful planning. It appears that the best ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 16 publications
(28 reference statements)
3
71
0
Order By: Relevance
“…In zoos, males are successfully maintained in bachelor groups particularly when introduced at a young age in similar age cohorts and when groups are limited in size to three individuals, on average [Stoinski et al, 2004b]. Groups may experience higher rates of success when composed of mother-reared individuals [Stoinski et al, 2004b] who have tolerant personality profiles, illustrated by high rates of affiliative behavior and low rates of agonistic behavior .…”
Section: Why Are Special Facility Design Recommendations Needed For Hmentioning
confidence: 97%
See 2 more Smart Citations
“…In zoos, males are successfully maintained in bachelor groups particularly when introduced at a young age in similar age cohorts and when groups are limited in size to three individuals, on average [Stoinski et al, 2004b]. Groups may experience higher rates of success when composed of mother-reared individuals [Stoinski et al, 2004b] who have tolerant personality profiles, illustrated by high rates of affiliative behavior and low rates of agonistic behavior .…”
Section: Why Are Special Facility Design Recommendations Needed For Hmentioning
confidence: 97%
“…Successful propagation of Western lowland gorillas in North American zoos has led to a growing need for bachelor gorilla groups [Stoinski et al, 2004b]. The most recent Population Analysis and Breeding Plan for the Western Lowland Gorilla SSP [Lukas et al, 2007] reports that of 173 male gorillas in the population, 58 are housed in 20 bachelor groups at 16 zoos.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, the United States and Japan there have been a large number of studies on primate cognition (Hopper, 2017). However, very little research is carried out on personality, and even less on the link between personality and behaviour (Stoinski et al, 2004). Moreover, methodological studies, such as validating personality-trait ratings with behavioural observations, are often the focus of this work.…”
Section: Behaviour Management and Conservationmentioning
confidence: 99%
“…This could lead to a reduction of aggressive encounters, because gorillas rated lower for Understanding were also more likely to engage in noncontact aggression (Kuhar et al, 2006). It has been suggested that gorilla groups should be formed when the apes are young for the best outcomes (Stoinski et al, 2004), so it is vital to understand any agerelated differences in personality, but this is not always possible in zoos (see Huskisson & Chism, 2018 (King, J. E., et al, 2008). In orangutans, Agreeableness declines with age, and while Extraversion also decreases as orangutans age, it does so differently from Chimpanzees (Weiss & King, 2015).…”
Section: Behaviour Management and Conservationmentioning
confidence: 99%